Electoral Governance of Campaign Materials: The Role of Bawaslu in Regulating Campaign Materials (APK) During Pilkada 2024 in Barito Utara - Kurniawan, Muhammad; Khair, Abdul; Putera, M. Luthfi Setiarno (Universitas Islam Negeri Alauddin Makassar, 2025)
This study analyzes the role of the Election Supervisory Agency (Bawaslu) of Barito Utara Regency in regulating campaign materials (APK) during the 2024 regional elections (Pilkada) in Muara Teweh City. The widespread use of APKs often leads to environmental and aesthetic concerns, particularly due to their placement in locations that violate existing regulations. Bawaslu Barito Utara holds the authority to monitor and enforce the proper installation of APKs in accordance with the regulations set by the General Elections Commission (KPU) and Bawaslu itself. However, this study identifies several challenges, including limited resources, inadequate coordination with relevant stakeholders, and the ineffective implementation of sanctions. The research employs an empirical legal method using a socio-legal approach, involving observation, interviews with key stakeholders, and analysis of legal documents. The findings indicate that although Bawaslu has carried out supervisory duties, its effectiveness remains hindered by structural and operational factors. The study recommends strengthening Bawaslu’s institutional capacity, particularly in terms of resources, and improving regulations to enable more effective law enforcement in future elections. These findings are expected to contribute to the enhancement of democratic processes and electoral governance in Indonesia.